Evaluating Change Management Frameworks: Insights and Implications for the Indian IT Sector (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The review consolidates existing research on change management frameworks and their relevance to the Indian IT industry. It critically examines the challenges and best practices associated with change management, highlighting the role of leadership, technology, and culture in driving organizational transformation. The article provides actionable recommendations for practitioners and future research directions.